Design Of Air Conditioning Control Equipment Using Arduino Microcontroller - Simanjuntak, Jamser; Steven Prayer Galintar S (Sean Institute, 2024)
Indonesia is a developing country with many people working in the agricultural and small industry sectors. Therefore, it is necessary to develop technology in small industries in order to create various new innovations. One example is the development of digital device technology, such as microcontrollers. The use of microcontrollers can have a positive impact on work ease and efficiency. For example, the design of a room temperature control system can provide significant benefits in supporting efficient work activities in the medium-sized industrial and office sectors. This study proposes a simulation design of a temperature control system along with its implementation in the form of a prototype of a room temperature control system based on an Arduino microcontroller. This system is equipped with the ability to display room temperature via an LCD screen. The system design stages start from system architecture analysis, and temperature control system planning, to prototype creation. The result of this study is a prototype of a temperature control system with a temperature display feature on the LCD; if the room temperature exceeds the maximum limit, the cooler will be active, and conversely, the cooler will turn off if the temperature is below the minimum limit. This system uses several devices, including Arduino, temperature sensors, coolers, and LCD screens to display temperature.